Impactos ambientais, revegetação e perspectivas de uso dos sistemas de dunas em setores da costa cearense - Borba, Eduardo Castro Menezes de (2010)
The determination of the vulnerability index of coastal dunes that make up in the central sector, has shown there is a gradient of susceptibility to degradation and erosion of the dune fields from the Paracuru city until you reach the Beberibe city. On this site we found the highest levels of occupation on dunes and counteroffer few management measures were observed with regard to preserve this environment. Due to recent increased production of wind power, driven by incentives from the federal government, we analyzed the damage that these developments cause in nature and beliefs of people in their surroundings. This analysis echoes that wind farms have a low potential impact, because the buildings hit the ground only 5% of the occupied area, but the concern is primarily due to soil compaction necessary to construct roads giving access to wind towers since this would cause the leaching of fresh water that is stored in the dunes aquifer. As a way to make a durable and sustainable method to control the dunes migration toward the installations of wind farms in this case was developed an experiment of spreading fragments in situ of three pioneer species of dunes plants belong different families. Where the grass Paspalum maritimum showed greater prominence in relation to Phaseolus panduratus (Leguminosae) and Ipomoea pes-caprae (Convolvulaceae), both by the higher survival as by growth.